Development of key wafer-level packaging technologies and design rules for MEMS and biomedical MEMS - Miao, Jian Min. (2009)
Three etching masking technologies of Cr/Au, Cr/Cu and PECVD amorphous silicon are developed for Pyrex glass micromachining in the hydrofluoric acid solution. Our study reveals that the residual stress, especially the tensile stress, in the mask layers is responsible for the pinholes on the glass surface and mouse bites formed at the etch edges of glass due to the breakage of highly stressed mask layers during the etching process. The Cr/Au metal mask can achieve a glass etch depth up to 100 m, however with number of pinholes and mouse bites due to the highly tensile residual stress in the Cr/Au layer. The Cr/Cu metal masking layer improves the glass etch quality by the reduced residual stress. Detailed studies have been done using the amorphous silicon film as a glass etch mask. The PECVD process and the subsequent annealing process have been optimized to reduce the compressive residual stress in the amorphous silicon layer. The maximum etch depth in the glass can be as high as 200 m almost without pinholes and mouse bites. To our knowledge, this is the best result reported in the literatures so far. Silicon is well known as an inert material in hydrofluoric acid and can be used during wet etching of glass as a mask with good results. We report on the optimization of a PECVD amorphous silicon layer as etch mask for deep Pyrex glass micromachining in hydrofluoric acid solution. Our study reveals that the residual stress, especially the tensile stress, in the amorphous silicon masking layer is responsible for the defects generated during the etching process. The PECVD process and the subsequent annealing process have been optimized to reduce the compressive residual stress in the amorphous silicon layer. The maximum etch depth of glass achieved is as high as 300 m. We also address the main issues related to wet micromachining of one of the mostly used BioMEMS materials - glass - and propose two optimized solutions for deep wet etching. As a result, 500 m-thick Pyrex glass wafer was etched using an etching mask consisting of low stress amorphous silicon (a:Si) and photoresist. Moreover, we report the successful through etching of 1 mm Pyrex glass wafer using a combination of low stress a:Si/SiC/photoresist mask. The fabrication of very high aspect ratio through-wafer copper interconnects by an innovative copper electroplating technique is reported. Completely void free electroplating in very deep (~500 µm) and narrow through-holes is accomplished by a proposed ‘aspect ratio dependent electroplating technique’. In this technique, electroplating parameters are continuously varied along with changing unfilled via depth. Continuously varying current density improves the local distribution of current as per the changing depth and helps in minimizing the void formation. Hydrophilic nature of via surface is also enhanced by wet surface treatment to improve the interaction between copper electrolyte and via surface. Very fine pitch (~80 m), through-wafer copper interconnects having aspect ratio as high as 15 are fabricated by the above innovative technique.